Factors Determining Adoption of Block Chain in the Insurance Industry: A Case of Kenya - Musyoki, Watson Kanuku; Shitanda, Douglas; Nganu, Margaret (International Journal of Science and Research (IJSR), 2020)
Blockchain is receiving increasing attention from academy and industry, since it is considered a breakthrough technology that could bring huge benefits to many different sectors. In 2017, Gartner positioned blockchain close to the peak of inflated expectations, acknowledging the enthusiasm for this technology. In this scenario, the risk to adopt it in the wake of enthusiasm, without objectively judging its actual added value is rather high. Insurance is one the sectors that, among others, started to carefully investigate the possibilities of blockchain. For this specific sector, however, the hype cycle shows that the technology is still in the innovation trigger phase, meaning that the spectrum of possible applications has not been fully explored yet. Insurers, as with many other companies not necessarily active only in the financial sector, are currently requested to make a hard decision, that is, whether to adopt blockchain or not, and they will only know if they were right down the years. This study seeks to establish the factors which determine successful adoption of block chain in the insurance industry. The study is descriptive in nature, with both qualitative and quantitative data. Stratified random sampling technique was used to select 16 companies out of the 52 insurance companies registered in Kenya, based on their domain of operation. The study identified several factors, which are the major determinants of the block chain adoption. They were categorized into four domains. Motivational aspect, Internal barriers, External barriers and Ecosystem barriers. Out of this research, it came out clearly that there is need for a framework on block chain adoption, putting into consideration the factors identified as the elements of the framework.
Keywords: Block chain; Insurance industry; block chain adoption; determinants; framework